Correlation between oral health behaviors and dental caries on substance use disorder : Study cross-sectional - Fadhila, Putri Khansa; Lestari, Sri; Asia, Rr Asyurati (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Drug abuse can cause dental and oral health problems such as dental caries. One of the contributing factors is the behavior of ignoring dental and oral hygiene. Several studies state that the incidence of dental caries in substance use disorder can be caused by a lack of dental and oral health maintenance behavior. This study aims to determine the association between oral health behaviors and dental caries in substance use disorder at the Rehabilitation Center of the National Narcotics Board Lido Bogor. Methods: This research method is analytic observational with cross-sectional design.  The minimum sample size in this study used the lemeshow formula and obtained 80 samples. The number of samples used in this study were 100 respondents. Data collection on oral health behaviors using questionnaires (knowledge, attitudes, and practices) and dental caries data using the WHO dental caries index. Data were analyzed using bivariate analysis and statistical tests using the Spearman correlation test. Results: The results showed that most respondents had oral health behaviors in the moderate category at 48%. The average DMF-T and dental caries prevalence of respondents were 9.4 and 97%. The results of the Spearman correlation test, obtained a correlation coefficient (r) of - 0.822 and a significance value p < 0.001 which shows that the two variables have a strong and significant relationship. The negative sign indicates that the better the respondent's behavior, the lower the dental caries index value and vice versa. Conclusions: There is a negative correlation between oral health behavior and dental caries on substance use disorder.KEY WORDS: Substance use disorder, oral health behavior, dental cariesKorelasi perilaku pemeliharaan kesehatan gigi dan mulut dengan karies gigi pada penyalahguna narkoba: Studi cross-sectionalABSTRAKPendahuluan: Penyalahgunaan narkoba dapat menyebabkan masalah kesehatan gigi dan mulut seperti karies gigi. Salah satu faktor penyebabnya adalah perilaku mengabaikan kebersihan gigi dan mulut. Beberapa penelitian menyatakan bahwa kejadian karies gigi pada penyalahguna narkoba dapat disebabkan karena kurangnya perilaku pemeliharaan kesehatan gigi dan mulutnya. Penelitian ini bertujuan untuk menganalisis hubungan antara perilaku pemeliharaan kesehatan gigi dan mulut dengan karies gigi pada penyalahguna narkoba. Metode: Metode penelitian ini adalah observasional analitik dengan rancangan cross-sectional.  Besar sampel minimum pada penelitian ini menggunakan rumus lemeshow dan didapatkan sebesar 80 sampel. Jumlah sampel yang digunakan dalam penelitian ini yaitu sebanyak 100 responden. Pengumpulan data perilaku pemeliharaan kesehatan gigi dan mulut menggunakan kuesioner (pengetahuan, sikap, dan tindakan) dan pengumpulan data karies gigi dengan pemeriksaan gigi dan mulut menggunakan indeks karies gigi WHO. Analisis data dilakukan menggunakan analisis bivariate dan uji statistic menggunakan uji korelasi Spearman. Hasil: Sebagian besar responden memiliki perilaku pemeliharaan kesehatan gigi dan mulut dengan kategori cukup sebesar 48%. Didapatkan DMF-T rerata dan prevalensi karies gigi responden adalah 9,4 dan 97%. Hasil uji korelasi Spearman, didapatkan nilai koefisien korelasi (r) sebesar -0,822 dan nilai signifikansi p<0,001 yang menunjukkan kedua variabel memiliki hubungan yang kuat dan signifikan. Tanda negatif menunjukkan jika semakin baik perilaku responden, maka semakin rendah nilai indeks karies giginya begitupun sebaliknya. Simpulan: Terdapat korelasi negatif antara perilaku pemeliharaan kesehatan gigi dan mulut dengan karies gigi pada para penyalahguna narkoba.KATA KUNCI: Penyalahguna narkoba, perilaku kesehatan gigi dan mulut, karies gigi